Mono-Herbal Recipes in Vangasena Samhita-A Review - Navami , A; Vivek , P; Manoj , Kumar N (International Research Journal of Ayurveda & Yoga, 2022)
Herbal drugs are a major part of Ayurvedic medicine, which is evolved as a system of practice from ancient period. Brihatrayee and Laghutrayee are today’s available classical texts. However, literature about Ayurveda has been created before & after these classical texts. Vangasena Samhita is one of such neglected but valuable text in between these two literatures. Vangasena Samhita or Chikitsasarasamgraha is a comprehensive work belongs to 12th century AD by Vangasena. This medical treatise is often quoted by the names Vangasena samgraha, Vangadatta or Sarvasiddhantasara. In Vangasena Samhita, it mainly deals with pathology, description of diseases along with the principles of treatment, different pharmaceutical preparations, prognosis and dietetics. In this treatise author contributes many mono-herbal recipes and formulations which are indicated in various disease conditions. Total herbal preparations in Ayurveda can be of mono herbal (single) or poly-herbal (multiple). Among them single drug herbal recipes are very effective as well as easy to prepare and which helps in reducing, the over usage of medicinal plants in preparing the compound formulations. A total of about 371 mono-herbal recipes can be seen in Vangasena Samhita. Some of such single drugs are Guduci, Pippali, Shunti, Amalaki, Vasa, Haritaki, Shigru, Eranda etc. in various disease conditions along with their anupana and the mode of administration in a systematic manner. The review has focused on easily available and easily applicable herbal remedies.